Multi-purpose cooperatives towards people empowerment and development - Jadloc, Zosimo A. 1932- (Giraffe Books, 2001)
A handbook designed to help community organizers, officers of cooperatives, group leaders and prospective cooperative members in their involvement in the activities in the cooperative movement. It contains guidelines on how members of a democratic society can be liberated and empowered to avoid financial and political exploitation.